UPAYA PENEGAKAN HUKUM OLEH POLRI DALAM PENANGANAN TINDAK PIDANA BERDASARKAN KEADILAN RESTORATIF TERKAIT TINDAK PIDANA LALU LINTAS - Hadi Nur; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2022)
The problem of attitude in traffic is a common phenomenon in big cities in Indonesia. The variety of vehicle traffic and the increasing number of vehicles that are faster than the increase in road infrastructure have resulted in various traffic problems such as congestion and traffic accidents. Several traffic crime problems that commonly occur in Indonesia are caused by traffic driving violations without paying attention to traffic signs, causing traffic accidents or disturbing fellow road users. UU no. 22 of 2009 regulates matters regarding traffic crimes as regulated in Chapter XX. The settlement of traffic accident criminal cases by the police through the Restorative justice system is a guideline in the peace process outside the judiciary by using mediation in achieving justice. The obstacle in implementing the concept of restorative justice faced by the police is the absence of consent from the victim or family to forgive the perpetrator.